The Reve’s Puzzle with Single Relaxation - Majumdar, AAK (Journal of Bangladesh Academy of Sciences, 2020)
This paper considers a variant of the Reve’s puzzle with n ( ≥ 1) discs which allows at most one violation of the “divine rule”. Denoting by S4(n) the minimum number of moves required to solve the new variant, an explicit form of S4(n) is given. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 211-212, 2019